Heroines of Health: Examining the Other Side of the “Splendid Little War” - Ingrid Gessner (European Journal of American Studies)
The Spanish-American War, dubbed the “splendid little war” by John Hay, began on April 25, 1898, and lasted until Spain signed the armistice on August 12, 1898. During the war death from infectious diseases caused seven times the number of fatalities as battle wounds. Although a patriarchal military system initially preferred male medical personnel, the Spanish-American War confirmed the competence of women in military service as nurses and doctors and led to the establishment of the permanent Army Reserve Nurse Corps in 1901. Drawing on historical documents and examples from material commemorative culture this article examines the textual, cultural, and rhetorical representation of the experiences of Acting Assistant Surgeon Anita Newcomb McGee and Army contract nurse Clara Louise Maass, who volunteered to participate in yellow fever experiments and died of the disease. The article argues that the experiences of McGee and Maass as active agents during the war exemplify struggles for successful emancipation during and after wartime and enable new ways of celebrating and commemorating female heroism.